Peranan Account Payable terhadap Kelancaran Pembayaran Supplier di Hotel Solia Zigna Kampung Batik Laweyan - Agung, I Gusti Ayu; Solikhin, Agus; Cindy Saputri, Sonnya Ayu (Excellent, 2025)
As the largest archipelago in the world, Indonesia has great tourism potential due to its rich natural and cultural diversity on each island. In the era of globalization, the tourism industry has become one of the main pillars of the global economy, and Indonesia realizes the importance of this sector in supporting its economy. One of the important aspects of the tourism industry is accommodation, which has a strategic role in the tourist experience. Hotel Solia Zigna Kampung Batik Laweyan in Solo City, a culturally attractive destination, is an example of how the hotel sector supports the tourism industry. However, the hotel faces challenges in financial management, particularly in the Account Payable function, which is responsible for managing payments to suppliers and ensuring operational smoothness. This research uses a descriptive qualitative method, where data collection involves interviews, observations, documentation, and literature studies. The participants in this study are one Finance Controller and two Account Payable staff. The purpose of this study is to determine how the supplier payment process and standard procedures are carried out at Hotel Solia Zigna Kampung Batik Laweyan, what documents are used in the payment process, and the obstacles faced by the Account Payable staff. The research results show that the Account Payable department has the main responsibility for paying bills from suppliers and non-suppliers and must ensure that the payment process runs smoothly to avoid operational disruptions. The main obstacle faced is the delay and loss of documents, which can be overcome through better coordination and a more structured recording system.